Best Practice Spectrum Renewal and Pricing : A Review of International Best Practice and the Lessons for the Government of Bangladesh - Friend, Graham (World Bank, Washington, DC, 2014)
The 15 year licenses of four mobile operators in Bangladesh; Grameenphone, Banglalink, Robi, and Citycell are due to expire in November 2011. The remaining two other mobile operators, state owned Teletalk and Airtel, were issued licenses in 2004 and 2005 and these are not due for renewal until 2019 and 2020 respectively. The World Bank has asked Coleago Consulting Limited (Coleago) to prepare a report on international best practice for spectrum renewal and pricing and to analyze the Bangladesh Telecommunication Regulatory Commission (BTRC) proposals in light of best practice. The mobile industry has changed dramatically in the intervening years and so license renewal provides regulators with the opportunity to update relevant regulation to better align the licensing framework and license conditions with the mobile industry of today and to accommodate future developments. In this report the author have surveyed a number of jurisdictions and examined both successful and not so successful spectrum renewal processes in order to derive a set of international principles of best practice for spectrum renewal and pricing. In doing so the author have also sought to identify best regulatory practice in a broader sense as successful spectrum renewal processes depend, in part, on being conducted within a robust and effective overall regulatory regime. This report covers: the process of spectrum renewal including both administered and market based approaches; and alternative methods for pricing spectrum.